KAJIAN PALATABILITAS BAKSO BERBAHAN DAGING SAPI SEGAR DAN DAGING SAPI BEKU IMPOR DENGAN LEVEL PENGGUNAAN SODIUM TRIPOLIFOSFAT YANG BERBEDA - Etty Nuri Hendrarti; Gatot Adiwinarto (Journal of Livestock Science and Production, 2018)
This research was conducted to study palatability of meatball with fresh and imported frozen beef as base material with varians level of sodium tripolyphosphates. This research used randomized block design with 6 treatments and 3 groups of time production periods.The treatments were 0,2% (A), 0,3% (B); 0,4% (C) of sodium tripolyphosphates addition  into fresh beef mixture and 0,2% (D), 0,3% (E); 0,4% (F) of sodium tripolyphosphates addition into thawed of imported beef mixture.  Data from hedonic method of organoleptic test in color, texture, aroma, hardness, elasticity and taste variable  analized by Kruskal-Wallis-non parametric method and continued by multiple comparison test when significant result  (P<0,05). The result showed that panelists prefered 0,2% (D) of sodium tripolyphosphates addition into thawed of import beef mixture and 0,2% (A), 0,3% (B); 0,4% (C) of sodium tripolyphosphates addition  into fresh beef mixture to 0,3% (E) and 0,4% (F) of sodium tripolyphosphates addition into thawed of imported  beef mixture (P<0,05)  in color, texture, hardness, elasticity and taste of meatball,  excep for aroma  was similar preferance (P>0,05) in aroma. The level  0,2%  of sodium tripolyphosphates addition into thawed of imported beef mixture for meatballs can improve the product functional properties effectively and recommended.Keywords: meatball, fresh beef, imported frozen beef, palatability, sodium tripolyphosphates